The Functions of the Research Officier in Trade Unions - Waisglass, Harry (Relations industrielles / Industrial Relations, 1966)
The author exposes the union approach to research from the perspective of the research departments functions, distinguishing the functions of the research officers from their activities, their methods and techniques.